Effects of package, storage period and locality on the quality of shorghum seeds - Filho, Francisco Lopes; Assunção, Marcos V.; Vieira, Francisco Valter (Pesquisa Agropecuaria Brasileira, 2014)
Shorghum seeds, Sorghum bicolor (L.) Moench, cv. EA-955 were packed in sealed metal cans, cloth and polypropylene bags and stored in natural conditions in four places in the state of Ceará, Brazil, namely: Fortaleza, Quixadá, Morada Nova and Ubajara, with the objective of determining the influence of package, locality and storage period on the seed physiologic quality. Each month seed moisture content was evaluated. Germination, vigor (root length) and seedling dry weight tests were used to evaluate seed quality. The treatments were arranged in a factorial design, where the factors were five periods of storage (0, 2, 4, 6 and 8 months) and three package types (sealed cans, cloth, and polypropylene) with four replications. During the storage period it was observed that metal can is the best in persevering the quality of the seeds. It was detected that seeds stored in Ubajara showed better quality than the seeds stored in other localities.